Analisis Keterampilan Teknik Pukulan Backhand Bulutangkis pada Atlet Usia Remaja Klub Pelatkot Kota Gorontalo - Saromeng, Yusril; Pramono, Harry; Irawan, Fajar Awang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to find out and analyze the level of badminton technique skills at PB Pelatkot Gorotalo City in 2023. The method used in this research uses a quantitative approach with a survey research design to get a systematic, factual, and accurate picture of the facts and characteristics. The data collection technique was done by direct observation, simulating internal matches for Gorontalo Pelatkot athletes. The population and sample in this study were PB Pelatkot Gororntalo City athletes, totaling 20 athletes: 10 male athletes and ten female athletes. The sampling technique in this research was total sampling. This research shows the badminton hitting technique skills in PB Pelatkot Gorontalo athletes. Short serves have a success rate of 95.40% in the "Very Good" category, long serves have a success rate of 94.68% in the "Very Good" category, lob shots have a success rate of 92.32% in the "Very Good" category, smashes have a success rate of 75, 92% are in the "Enough" category, and dropshot shots with a success rate of 67.38% are in the "Poor" category. In conclusion, provide knowledge and understanding regarding hitting techniques in badminton to athletes so that they can help provide appropriate treatment and support Keywords: backhand, badminto, hitting technique